Position Papers of Technical Working Groups on Six Clustered Agenda Items - Moro Islamic Liberation Front, * (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2009)
A document by the Moro Islamic Liberation Front (MNLF)